Effect of strobilurin fungicides on control of early blight (Alternaria solani) and yield of potatoes grown under two N fertility regimes - MacDonald, William; Peters, Rick; Coffin, Robert; Lacroix, Christian (Phytoprotection, 2007)
Early blight, caused by Alternaria solani, is a ubiquitous disease that can reduce potato yield. Adequate crop fertility and appropriate fungicide applications usually suppress the development of this disease. Field trials were established in Prince Edward Island to determine whether strobilurin analogs, namely azoxystrobin and pyraclostrobin, could suppress early blight of potatoes (cvs. Shepody and Russet Burbank) grown under two nitrogen (N) fertility regimes (high or low N). Azoxystrobin and pyraclostrobin were linked to significantly higher total tuber yield for Russet Burbank in 2003 and Shepody in 2004 when compared to plots receiving no strobilurin fungicides. No significant differences in total tuber yield based on N fertility were observed, although the high N rate decreased disease in Russet Burbank control plots in 2004. Due to an absence of early blight in 2003, the increase in Russet Burbank yield may be attributed to the physiological and developmental alterations brought about by strobilurin products in treated plants. In 2004, early blight was severe in inoculated control plots, but it was significantly suppressed in plots having received azoxystrobin or pyraclostrobin, regardless of the cultivar type or fertility regime. Therefore, to prevent unnecessary N inputs, growers need to supply only the necessary N amount to optimize tuber yields and manage early blight with fungicides.